Implementation of Health Education Program on Diarrhea Prevention in Mothers of Toddlers - Dhitta Ayu Parlitta; Ekayanti Ekayanti; Susy Agustiani (Indonesian Journal of Global Health Research, 2025)
Diarrhea is one of the main causes of death in toddlers and is a significant factor in cases of malnutrition in this age group. Government efforts to overcome health problems, especially infectious diseases, are realized through various programs, one of which is the role of the Public Health Center (Puskesmas) in controlling and eradicating diarrheal diseases. This study aims to determine the effectiveness of the health education program in reducing the incidence of diarrhea in toddlers at Posyandu Mawar Sunter, North Jakarta in 2024. This study used a quasi-experimental design with a pre-test-post-test only model. The sampling technique used total sampling with a sample size of 35 samples. The study was conducted at Posyandu Mawar Sunter, Jakarta in November-December 2024. The results of the Paired Samples Correlations test obtained a significant value of 0.000 <α value of 0.05, so it can be concluded that the health education program on preventing diarrhea in toddlers at Posyandu Mawar Sunter, North Jakarta in 2024 was very influential.